CDR 2021
DOI: 10.20517/cdr.2020.93
|View full text |Cite
|
Sign up to set email alerts
|

How to win the ovarian cancer stem cell battle: destroying the roots

Abstract: Ovarian cancer has the highest mortality rate among gynecologic malignancies. The combination of cytoreductive surgery and chemotherapy is the standard regimen for the treatment of ovarian cancer. The initial treatment is usually effective, but many patients with ovarian cancer experience recurrence, and treatment options for recurrent disease remain challenging. Cancer stem cells (CSCs) are suggested to play an essential role in cancer recurrence after initial chemotherapy. Furthermore, they are of great inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 108 publications
(134 reference statements)
0
13
0
Order By: Relevance
“…At the cellular level, analysis of cisplatin-sensitive vs. cisplatin-resistant tumors revealed that resistant cells descend from pre-existing minor subpopulations in the primary tumor [16], which most likely represent cancer stem-like cells (CSCs) [17][18][19][20][21][22][23]. CSCs possess high resistance to cytotoxic and genotoxic effects, are capable of self-renewal, and asymmetric division that generates a progeny of fast-proliferating bulk tumor cells [24]. CSCs possess a high tumorigenic potential and can re-initiate tumor development after chemotherapeutic treatment [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, analysis of cisplatin-sensitive vs. cisplatin-resistant tumors revealed that resistant cells descend from pre-existing minor subpopulations in the primary tumor [16], which most likely represent cancer stem-like cells (CSCs) [17][18][19][20][21][22][23]. CSCs possess high resistance to cytotoxic and genotoxic effects, are capable of self-renewal, and asymmetric division that generates a progeny of fast-proliferating bulk tumor cells [24]. CSCs possess a high tumorigenic potential and can re-initiate tumor development after chemotherapeutic treatment [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The cancer cell populations derived from a single patient are highly diverse [ 2 , 3 ]. Cancer stem cells (CSCs), the subpopulation of neoplastic cancer cells able to self-renew [ 4 , 5 ], contribute to chemotherapy resistance [ 2 , 5 , 6 , 7 ]. CSCs have been detected in OC tumors in the early and advanced stages before and after the conventional treatment [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 188 , 189 Few CSC markers, including ALDH1, CD44, CD117, and CD133 are considered to be useful predictive or prognostic biomarkers of OC. 190 The platinum-based chemotherapy resistance and tumor cell stemness is associated with the recurrence in HGSOC. In an aggressive murine model of OC, the stem phenotypes with a gain of KRAS , MYC , and FAK genes were found to be associated with intrinsic platinum resistance and tumorsphere formation.…”
Section: Introductionmentioning
confidence: 99%